Supply and demand of Data Science skills in South Africa - Mindu, Nkululeko (My University, 2021)
The Fourth Industrial Revolution is redefining industries and the world as we know it. At the heart of the revolution is an explosion and the democratisation of data. Oftentimes organisations need to understand or make use of this plethora of data to make decisions that drive business imperatives. Unique skill sets are required to enable organisations to thrive in the Fourth Industrial Revolution. Within this context, the study explores the Data Science profession through the lenses of skill supply and skill demand. The study reviewed the curriculum of Data Science training programmes, both university and non-university programmes were considered. The study then explored the skills currently being offered by incumbent Data Scientists by reviewing the profiles of Data Scientists on LinkedIn and looking at their featured skills as well as the academic background of these individuals. The demand for Data Science skills were then explored by looking at job posts for Data Science roles. Lastly to further explore skills in supply and the usage of Data Science skills in South African organisations, the study surveyed Data Science professionals, with a sample of 112 professionals being used. A conceptual competency framework was used to categorise the skills offered in the training programmes, skills supplied by incumbent Data Scientists and skills demanded by South African organisations. This was with a view of triangulating the skills from these different avenues and identifying the type of skills being emphasised. Results indicate a strong emphasis on quantitative and technology skills in the training programmes, skills by incumbent Data Scientists and skill requirements from organisations, when categorising according to the competency framework. There is also a strong emphasis on Data Tools such as Python, SQL, and R in the Data Science profession. It could be useful to consider different categories of Data Scientists and create specialised paths for the professionals. The broadness of the Data Science profession could benefit from making it a registered profession to create a unified understanding of the profession from all stakeholders from a skill supply and demand perspective
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Digital Business), 2021
Keywords: Supply and demand; Data science; South Africa; Fourth Industrial Revolution; SDG-9: Industry, innovation and infrastructure